Fábulas de Iriarte traduzidas para adultos: uma retradução comentada do espanhol ao português - Rosas, Clarissa (2022)
Tomás de Iriarte was one of the main Spanish fabulists, author of seventy-six fables structured in verses, with rhymes and metrification, published in the 18th century. These fables were translated into European Portuguese shortly after their first Spanish publication. In Brazil, the circulation of Iriarte’s fables was small and is currently restricted to six fables, aimed at children, which are part of anthologies or were published individually in the 20th century, and appear in libraries or second-hand book collections. In this context, in view of the relevance of Iriarte’s fables as a representative of the Spanish fable and its scarce diffusion in Brazil, this work aims to retranslate a substantial and representative selection of fables followed by comments. Iriarte’s work is called “Fábulas literarias” (Literary fables), and the adjective “literary” in the title is not for nothing: it is due to the fact that his fables deal with themes that are part of the world of literature, such as literary works, authors, translators, quotes, etc. Due to the peculiar themes it addresses, unlike the more general themes commonly dealt with in fables since its remote origins, Iriarte is recognized and appreciated especially for his originality. Considering that this theme is more focused on an adult audience and based on Rousseau’s thesis that the fable genre is not appropriate for children, the translation proposed here is aimed at the adult audience. This decision implies a direction for the translation, which could then be free of issues such as accessible vocabulary and simple syntactic constructions – what would be a necessary reflection if the children’s audience was the target of the translation. The aimed public established for the translation was a determining factor for the flexibility of retextualization: when we considered that our target reader should be able to enjoy a more erudite text, a wider range of vocabulary and syntactic constructions was made available to us. Thus, as expected, the content presented itself as a more flexible facet for translation than the form, which in our case followed stricter standards such as metric and rhyme. The thesis is divided into five chapters: the first deals with the literary context, which involves the fable genre, the target audience of the fables, a presentation of Iriarte as an author and translator, a presentation of his fables and a survey of Iriarte’s fables translations into Portuguese; the second concerns the theoretical framework, which addresses commented translation, retranslation, translation strategies, form and content in verses translation and culture-specific items; the third presents the methodological procedures, which are divided into stages of the adopted methodology, selection of the corpus for translation, translation project and proposed scheme for comments; the fourth brings the translations and the fifth, the comments.